Environmental Pollution and Global Climate Change: A Review - Suman Verma; Everest Shiwach; Sandeep Kumar; Pramod Kumar (International Journal of Engineering and Management Research, 2019)
Air pollution is an extremely serious problem for the modern industrialized world. Primary pollutants include carbon oxides, nitrogen oxides, sulfur oxides, particulates, lead, and volatile organic compounds. Secondary pollutants arose from chemical reactions when pollutants are exposed to sunlight such as photochemical smog. Ozone is one of the major secondary pollutants, also a greenhouse gas. Tropospheric ozone (O3) formation depends on the presence of methane, carbon monoxide, or volatile organic compounds (VOCs) and nitrogen oxides (NOx = NO + NO2). Black Carbon is also major secondary pollutants that emitted mainly from burning plants and fossil fuels. Air pollution and climate change are closely related. The main sources of CO2 emissions are extraction and burning of fossil fuels. They are not only key drivers of climate change, but also major sources of air pollutants. Furthermore, many air pollutants that are harmful to human health and ecosystems, also contribute to climate change by affecting the amount of incoming sunlight that is reflected or absorbed by the atmosphere. The greenhouse effect is a process that results in global warming. Global Climate Change and global warming is a real threat now for survival and existence of mankind on the planet Earth.